VALIDITE DES EPREUVES DE COMPREHENSION DU TEXTE ET DE MATHEMATIQUE DESTINES AUX ELEVES DE SIXIEME ANNEE PRIMAIRE DU TERRITOIRE ISANGI EN REPUBLIQUE DEMOCRATIQUE DU CONGO - JOHN, LOELA GEUTU (IJRDO - Journal of Social Science and Humanities Research, 2022)
This article consisted in conceiving two tests adapted to the level of the pupils of the terminal degree of the primary schools in RDC. It is about a test of mathematical and of a French test, precisely the understanding of the text. To close to the tests applied to the pupils of sixth primary year of the territory of Isangi in Democratic Republic of Congo, these two tests gave of trè good results